Examining the Impact of Social and Psychological Influences on Consumer Purchasing Decisions: A Case Study of Cahaya Fashion Warujayeng - Imroh, Alvina; Kusumaningtyas, Dian; Raharjo, Itot Bian (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2024)
This study explores how social and psychological factors influence purchasing decisions at Cahaya Fashion Warujayeng, employing a quantitative approach to gather data from 150 customers through structured questionnaires. The survey covered demographic information, as well as social factors like peer influence and family recommendations, and psychological factors such as perception and motivation. Regression analysis was conducted to identify significant predictors of purchasing decisions. The results indicate that social factors—specifically peer influence (β = 0.45, p < 0.01) and family recommendations (β = 0.37, p < 0.05)—significantly impact purchasing decisions. Psychological factors also play a critical role, with perception (β = 0.30, p < 0.05) and motivation (β = 0.25, p < 0.05) showing significant effects. These findings contribute to existing literature by integrating these factors within the context of a regional fashion store. The study advises fashion store managers to incorporate these insights into marketing strategies aimed at enhancing customer satisfaction and store performance. Practical implications include utilizing social proof through customer testimonials and cultivating a positive store atmosphere to positively influence customer perception and motivation. Future research should expand on these findings by exploring different contexts and larger sample sizes to validate and extend the understanding of consumer behavior. Additionally, exploring additional psychological dimensions such as emotional responses and brand loyalty could offer further insights into consumer behavior dynamics.